1996
DOI: 10.1074/jbc.271.46.29312
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Topology of α- and β-Subunits of Na+,K+-ATPase Derived from β-Galactosidase Fusion Proteins Expressed in Yeast

Abstract: Various models of the transmembrane topology of the Na ؉ ,K ؉ -ATPase predict either 8 or 10 membrane spans for the ␣-subunit and one to three membrane spans for the ␤-subunit. Structure/function analysis, however, requires precise knowledge about the folding of enzymes. Therefore, the intention of this work was to establish a transmembrane topology model for the subunits of Na LGGYP 236 ) of the dog ␤-subunit. The fusion constructs were expressed in yeast cells for studies on the localization of the fused re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…In one study using carboxyl-terminal truncations of the ␣-subunit expressed in yeast (14), the authors place Ala 789 close to the cytoplasmic side and Met 809 in the extracellular loop between M5 and M6. Their results are compared with another 10 membrane-spanning model proposed earlier by Karlish et al (7), who placed Ala 789 close to the extracellular part of M5.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study using carboxyl-terminal truncations of the ␣-subunit expressed in yeast (14), the authors place Ala 789 close to the cytoplasmic side and Met 809 in the extracellular loop between M5 and M6. Their results are compared with another 10 membrane-spanning model proposed earlier by Karlish et al (7), who placed Ala 789 close to the extracellular part of M5.…”
Section: Figmentioning
confidence: 99%
“…This is undoubtedly because of the extra mobility and flexibility of the region compared with the amino-terminal region, so that methods that involve disruptive procedures (such as proteolysis and peptide bond cleavage) are prone to generate artifactual observations. We began our investigation in this region by introducing a cysteine at residue 793, which has been predicted to be a part of the M5M6 external loop (7,14,17). Previous studies have shown that the M5M6 hairpin, following proteolysis and removal of K ϩ ions (at 37°C), is released from the membrane (32) to the extracellular space (33).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Either four or six C-terminal traverses have been proposed based on hydropathy plots and various experimental approaches (for recent investigations on Na ϩ K ϩ -ATPase see [2,3]). Furthermore, the precise part of the polypeptide chain which is embedded in the membrane is often uncertain (see e.g.…”
mentioning
confidence: 99%